Essays in developmental economics: The role of information and access to financial services in changing financial and employment behaviour and the resulting impact on household welfare - BEDI, TARA (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2018)
This thesis contains three essays that analyse the financial access and information awareness constraints faced by individuals and household in developing countries for managing income uncertainty and income shocks. The underlying theme throughout this thesis is about addressing how people manage these constraints and how this affects their welfare outcomes. Each essay uses micro level data at the individual and household level in different country contexts to analyse constraints to poverty alleviation. Through this analysis, these essays add to the empirical evidence by providing some insight into the potential tools and mechanisms that help households manage income variability and shocks. In chapter 1 of this thesis, a more detailed introduction is provided. Chapter 2 considers the impact of income uncertainty on the types of savings products agriculture dependent individuals in Kenya use. For the analysis, this chapter uses the FinAccess 2016 individual level cross-sectional data from Kenya, which is nationally representative, merged with the Famine Early Warning Systems Network (FEWSNET) rainfall data, from Kenya. Income uncertainty is proxied by recent changes in the coefficient of variation (CV) of rainfall for both the long and short rainy seasons. This chapter shows that agricultural dependent individuals respond to income un- certainty through differentiated revealed preferences for formally regulated, credit enabling and less liquid savings products. The results are robust to different time periods, various model specifications, and find that for non-agriculture dependent individuals, changes in climate variability has no effect on preferences for formally regulated or credit enabling savings products. The findings of this paper add a new dimension to our understanding of the use of financial products in low and unpredictable income settings. Chapter 3 exploits an exogenous change in the availability of credit for women in Viet Nam to look at the gender differentiated impact of credit on individual and household welfare. This chapter uses the Vietnamese Access to Resources Household Survey (VARHS), an extensive panel dataset that tracks the same 2,108 households for the period 2008 to 2016. Household fixed effects analysis is used to explore how access to credit and the level of credit supplied impacts on the allocation of female time and their investment decisions on their income generating activities. This chapter also explores whether credit in the hands of women versus men affect household welfare outcomes differently. From the analysis, this chapter finds that greater access to credit increases the number of days that women work in agriculture and home enterprise activities, while also changing the inputs women use in their income generation activities. Next, it finds that an increase in the relative amount of loans in the hands of women versus men negatively impacts income per capita and food expenditure in the current period. This chapter does find some positive correlations between increased credit access for women with child welfare outcomes, where increased access for women is correlated with a decrease in the time male children spend working in agriculture activities. This chapter contributes to a growing literature that explores the impact of access to credit on individual and household welfare outcomes and in particular whether credit in the hands of women compared with men matters. Chapter 4 addresses whether the direct and public provision of information to citizens affects the implementation of anti-poverty programs. This chapter uses the Young Lives panel dataset from India for the period of 2006 to 2014, that collects detailed demographic, consumption, income and occupation information at the individual and household level. This chapter exploits the variation in the implementation of an accountability intervention on the Mahatma Gandhi National Right to Employment Guarantee Act (MGNREGA) in Andhra Pradesh, India, to explore empirically whether MGNREGA outcomes change for households who are exposed to the information campaign and organised into groups. The main result from this chapter is that households in treatment areas are given more days of work, which translates into a smaller gap between the days they are entitled to and the the days they get supplied to work. The days worked under MGNREGA by households in treatment areas are rationed 24.6 percent less than for those in non-treatment areas. This essay adds to the empirical literature by showing that an information intervention to beneficiaries, who are empowered through being in a group setting, can increase the accountability of a program and how it is implemented. Chapter 5 concludes this thesis.
APPROVED
Keywords: Financial inclusion; Precautionary savings; Gender; Viet Nam; Household welfare; Child labor; Income shocks; Rainfall; Administrative processes; Corruption; Information and Knowledge